ANALISIS PENGARUH FEEDING PADA PROSES GRINDING JOURNAL TERHADAP NILAI KUALITAS CAMSHAFT TYPE 2TNV70 PASCA IQT - ARIES ABBAS; SUDJA RIZKI MAULANA (CV KULTURA DIGITAL MEDIA, 2021)
Research in the field of machining in testing the level of roughness needs to be done to get good results in the machining process. The purpose of this study was to determine the effect of variations in feeding on the surface grinding process on the surface roughness and hardness of S45C carbon steel that has gone through processes including induction, quenching and tempering and to compare which feeding variation has the lowest level of roughness. The research method used is an experimental method in the form of giving a variety of feeding which is tested on 4 samples in the surface grinding process. The number of variations given is 0.2mm/min, 0.4mm/min, 0.8mm/min, 1.2mm/min. The test results obtained are in the form of roughness values and hardness values on specimens that have been previously tested. The results showed that there was a change in the roughness value that occurred during the grinding process by applying a 0.2mm/min feeding variation resulting in an average value of 1.33683333µ, a feeding variation of 0.4mm/min producing an average value of 1.27068333µ, a feeding variation of 0.8mm/min producing an average value of 1.27068333µ. the average value is 1.29633333µ, the variation of feeding 1.2mm/min produces an average value of 1.39458333µ and there is no significant change in the surface hardness value in the surface grinding process. The tools used in this study were the Mitutoyo SV2100 rougness tester to determine the roughness value, and the Sonohard SH22 hardness tester to determine the hardness value. The data that has been obtained are then analyzed using descriptive statistics where the data are presented in the form of tables and graphs. after grinding. This shows that there is an effect of giving different variations of feeding the surface grinding process to the surface roughness value.